ANALYSIS OF THE CAUSES OF REPEATED FINDINGS IN AUDITS OF LOCAL GOVERNMENT FINANCIAL REPORTS: THE PERSPECTIVE OF THE BPK AUDITORS OF THE NORTH SUMATERA PROVINCE REPRESENTATIVE OFFICE - Victor Efendi; Eka Nurmala Sari (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the causes of recurring findings in the audit of local government financial reports from the perspective of auditors from the Supreme Audit Agency (BPK) Representative Office of North Sumatra Province. The phenomenon of recurring findings indicates that audit recommendations have not been fully followed up effectively by local governments. This condition has the potential to reduce the quality of local financial governance, hamper public accountability, and affect the effectiveness of local budget management. This study uses a descriptive qualitative method with a field study approach through in-depth interviews, observation, and documentation. Research informants consisted of auditors from the BPK Representative Office of North Sumatra Province who have experience in auditing local government financial reports. Data analysis techniques were carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that weak management commitment, weaknesses in SPIP (Standard Implementation Implementation System), limited human resource competency, administrative follow-up, and regulatory complexity are the main causes of recurring findings. Recurring findings are seen as indicators of suboptimal governance and internal oversight of local governments.